Pendampingan Saksi Dalam Tindak Pidana Korupsi - Leasa, Elias Zadrach; Latumaerrisa, Denny (MATAKAO Corruption Law Review, 2023)
Introduction: The investigation process of a suspect in a criminal case of corruption begins with the examination of a witness. The testimony of the judgment of the judgment is absolute. In addition to the threat of punishment for corruption over five years, and the testimony by the witnesses if not, of course, the testimony is given by the witnesses, According to the investigator, the witnesses are identified as a suspect in a criminal case of corruption. Purposes of the Research: Examining and analyzing forms of assisting witnesses by legal counselors in case of corruption crimes. Methods of the Research: The type of research used is normative research focused on giving systematic explanations that govern a particular category.The problem's approach to the law and conceptual approach. The gathering of legal material through primary legal material is then associated with secondary legal material.The management and analysis of legal materials is qualitatively deciphered. Results of the Research: Witness and victim protection laws specifically in chapter 2 indicate that these laws provide protection to witnesses and victims in all criminal proceedings in the judicial environment..From the sound of this chapter means against witnesses at all levels need protection, In this case, legal protection..In chapter ii, u psk in chapter 5 verse (1 ) a witness and victim have rights, One of them is free from question, and one of them is a witness., Should also be given by the prosecutor as an investigator in the corruption crimes., But sometimes they don't provide protection and rights as witnesses..To do that requires a witness accompanied by legal counsel or advocates in the process of investigating crimes of corruption in order to protect the rights of witnesses.